EFFECT OF DIFFERENT LEVELS OF SOAKED-WATER BARLEY AND FABA BEAN (MINOR) AS A PARTIAL SUBSTITUTE FOR MAIZE AND SOYBEANS IN GROWTH AND PRODUCTION OF QUAIL'S DIETS - Samir Hameed Majeed; Firas Khalil Ibrahim; Malik Mohamad Shukri; Salim thanon younis (Mesopotamia Journal of Agriculture)
The study was carried out in the Poultry farms/ Nineveh Research Department, by using 756 unsexing quail birds two weeks aged, distributed into nine experimental treatments with 3 replicates per treatment, each contained 28 birds, primary live weight 63.8 g, birds was fed on growth and production diets depending on growth stage. Results showed a significant improvement (P< 0.05) for soaked-water barley (SWB) treatments 10% and 20% on weight gain g/ bird (WG) and feed conversion ratio (FCR), FCR g food/g egg, egg production% for first four weeks of production, hatching% from total eggs for the first four, second and third weeks of production. Mathematic difference showed for the rest of the traits. The levels of Faba Bean (FB)  FB minor   10% and 20% had a negative and significant effect (P <0,05) on the WG and FCR at 3-5 weeks age, FCR for the first four weeks of production and eggs production %, a positive improvement (P < 0.05) for FCR and egg production% for third four weeks of production.